"Australopithecus afarensis" and A. Africanus: Critique and an alternative hypothesis - Tobias, Phillip V. (Bernard Price Institute for Palaeontological Research, 1980)
During the seventies, a succession of East African discoveries has been claimed to represent the "true" ancestral line of modern man, thus relegating A. africanus, and especially its Transvaal subspecies, to a subordinate role in hominid phylogeny. The latest such attempt has been the claim of Johanson and his co-workers that the 3, 7-2,6 My-old hominids of Laetoli in Tanzania and of Hadar in Ethiopia represent a new species, "A. afarensis", which led to H. habilis, whilst A. africanus represents early stages in a specialized side-branch leading to A. robustus and A. boisei. A critique of the diagnostic criteria of "A. afarensis" reveals that on the available evidence, the Laetoli and Hadar fossils cannot be distinguished at specific level from A. africanus transvaalensis. Furthermore, it is by no means clear that the pooling for statistical and comparative purposes of the Hadar and Laetoli fossils is justified. Hominids from the two sites are separated by about 800 000 years and about 1 600 km as well as by morphometric differences. As an alternative hypothesis, it is proposed that the Laetoli and Hadar hominids belong to the same lineage as that represented by the hominids of Makapansgat Members 3 and 4 and of Sterkfontein Member 4. Moreover, it is hypothesized that the Laetoli and Hadar hominids cannot be separated morphologically from A. africanus and that they represent two new subspecies of that species. Since "A. afarensis" is tied to a Laetoli specimen as holotype, only the Laetoli specimens should be designated A. africanus afarensis (though A. africanus tanzaniensis suggested by the author in 1978 would have been a more appropriate nomen) and the Hadar fossils A. africanus aethiopicus. These newest East African discoveries afford strong confirmation of the hypothesis that A. africanus is the common ancestor of the two later hominid lineages, A. robustuslboisei and Homo, leading from H. habilis through H. erectus to H. sapiens.
Main article
Keywords: Australopithecus; africanus; afarensis